Palynological study of pre-Siwalik sediments in Sub-Himalaya of central Nepal - Pradhan, Upendra Man Singh; Sharma, Shardesh Raj (Journal of Nepal Geological Society, 2003)
The pre-Siwalik sediments arc exposed in the inner Terai valley of central Nepal. The sediments occur within the Lower Siwalik and lie to the north of Marin Thrust. Slices of pre-Siwalik sediment might have brought up by thrusts. Since no fossils have been reported from these pre-Siwalik rocks, their age is referred to range from Gondawana to Miocene. In this paper, an attempt is made to determine the stratigraphic position and age based on the palynological study. A number or spores and pollen are recorded from the samples. However, the palynomorph assemblages in the samples include only stratigraphically long-ranging taxa (Eocene to Quaternary). The identified Compositae type along with Aabiespollenites, Caryapollenities, Psilamonocolpites, Retitricopites etc. arc found belonging to Miocene or younger. Zoncostites ramonae (mangrove) is assigned to be Late Eocene or younger age where as the Dinocyst Lingulodinium machaerophorum suggests the sample belonging to Tertiary or younger. Besides the pre-Siwalik outcrops are lithologically correlable with the red beds of Murree of India and Pakistan that arc assigned as Oligocene-Miocene age. Hence, considering the palynomorph assemblages, its recommended age and paleo-environment including the lithological correlation, the pre-Siwalik sediments of the present area must have deposited in Tertiary time and probably may range from Oligocene to Miocene.